Metastatic Melanoma to the Urinary Bladder: A Rare Cause of Visible Haematuria - Olawale Ogunremi; Dinelle Sirjuesingh; Aniket Deshpande (Case Reports in Urology)
Bladder metastasis from cutaneous melanoma is a rare pathology. A 79-year-old woman presented to the haematuria clinic on account of painless visible haematuria. Ten years prior to this index presentation, she was diagnosed with melanoma on her right thigh following a total excision of the skin lesion. Cystoscopy showed a pigmented bladder tumour, and the histology report following a transurethral resection was consistent with metastatic melanoma, and further imaging revealed metastasis to the lungs, adrenals, and lymph nodes.